Effects on intermittent postural control in people with Parkinson's due to a dual task - Marco-Ahulló, Adrià; Mayordomo, T.; Sales, A.; Pellicer-Chenoll, M.; Villarrasa-Sapiña, Israel; Melendez, J. C. (Human Movement Science, 2022)
Objectives: The aim of the present study was to determine the effects of performing a dual task on the sway density plot parameters in Parkinson's disease and control subjects.& nbsp;Methods: A cross-sectional design was used to establish differences in the mean peak, mean time, and mean distance between a group with Parkinson's disease and a control group without Parkinson's disease. The subjects performed, in a unique measurement session, two trials under three different randomized conditions: i. eyes open, ii. eyes closed, and iii. Eyes open with foam base. One trial was performed as a single task (i.e., the subjects completed one of the balance test), while the other trial was performed as a dual task (i.e., the subjects performed a cognitive task at the same time that they maintained the static balance).& nbsp;Results: There was a group x dual task x condition effect in mean peak (F-1.5,F- 51.1 = 5.21; p = 0.015; eta(2)(p) = 0.13) and mean time (F-1.4,F- 47.3 = 4.43; p = 0.03; eta(2)(p)& nbsp;= 0.11) variables. According dual-task cost analysis, there was a main effect of the condition (F-6,F-134 = 2.44; p = 0.05; eta(2)(p) = 0.34) on MD (F-2,F-68 = 6.90; p < 0.01; eta 2p = 0.17).& nbsp;Conclusions: This result indicates differences in the dual task interference in the postural control mechanisms between the Parkinson's disease population and healthy pairs. For easy dual tasks, the Parkinson subjects used anticipatory control responses for longer periods of time, and for more difficult tasks, their control strategy did not change regarding single balance task.
Keywords: balance; quiet standing; neuroscience; motor control; motor skills; JCR; Scopus